PERGESERAN FUNGSI HADIS DI MEDIA SOSIAL: Kajian Mediatisasi Hadis di Indonesia - Perdana, Tazkia Anugraheni; Alfika Inayatul Masruroh (Holistic al-Hadis, 2023)
Social media plays a big role in the process of mediatising hadith in Indonesia. Instagram, Tiktok and Twitter are the social media used by most Indonesians. In the digital era, hadith is conveyed through these social media. The delivery is considered more effective because it can reach more audiences. This paper aims to see how the mediatisation of hadith on social media, especially in Indonesia, as well as the response of netizens to the mediatisation of hadith spread on social media. The results of this study show that the form of hadith mediatisation on social media is influenced by the goals and intentions of the account owner. The purpose and intention of the account owner are reflected in the hadith and narrative used in the content. Meanwhile, hadith content that has a lot of responses from netizens is content that tends to blend the Islamic Shari'ah derived from hadith with the reality in society.